Determination of the Enantiomerization Barrier of Midazolam in Aqueous Conditions by Electronic Circular Dichroism and Dynamic Enantioselective HPLC/UHPLC - Francesca Romana Mammone; Daniele Sadutto; Eleonora Antoniella; Marco Pierini; Roberto Cirilli (Molecules)
Midazolam is a benzodiazepine that is utilized for the induction of anesthesia and the facilitation of procedural sedation. Despite the absence of stereogenic centers, the non-planar seven-membered ring devoid of reflection symmetry elements confers planar stereogenicity to the molecule. Due to the rapid conformational inversion of the Rp and Sp enantiomers, which occurs via a simple ring flip, high-performance liquid chromatography (HPLC) enantiomeric separation is restricted to sub-room temperature conditions. In this study, the energy barriers for the racemization of midazolam at five distinct temperatures and in acetonitrile/water mixtures were determined by monitoring the decay of the circular dichroism signal at a specific wavelength over time. The kinetic and thermodynamic data obtained were compared with those determined by dynamic enantioselective high-performance liquid chromatography using the Chiralpak IG-3 chiral stationary phase, which contains the amylose tris(3-chloro-5-methylphenylcarbamate) as the selector. The temperature-dependent dynamic HPLC of midazolam was carried out at the same temperatures and with the same aqueous mixtures used in parallel kinetic off-column experiments. To simulate dynamic chromatographic profiles, a lab-made computer program based on a stochastic model was utilized. The results indicated that the moderate influence of the stationary phase resulted in a slight increase in the activation barriers, which was more pronounced as the time spent in the column increased. This phenomenon was found to be mitigated when switching from a 250 mm × 4.6 mm, 3 µm, Chiralpak IG-3 column to a 50 mm × 4.6 mm, 1.6 µm, Chiralpak IG-U UHPLC column. The outcomes obtained under UHPLC conditions were found to be more closely aligned with those obtained through the ECD technique, with a discrepancy of only 0.1 kcal/mol or less, indicating a high degree of concordance between the two methods.